Visualizing Virus Assembly Intermediates Inside Marine Cyanobacteria - Dai, Wei (2013)
Cyanobacteria are photosynthetic organisms responsible for ~25% of organic carbon fixation on earth. These bacteria began to convert solar energy and carbon dioxide into bioenergy and oxygen billions of years ago. Cyanophages, which infect these bacteria, play an important role in regulating the marine ecosystem by controlling cyanobacteria community organization and mediating lateral gene transfer. Here we visualize the maturation process of cyanophage Syn5 inside its host cell, Synechococcus, using Zernike Phase Contrast (ZPC) electron cryo-tomography (cryoET)(1,2). This imaging modality yields significant enhancement of image contrast over conventional cryoET and thus facilitates the direct identification of subcellular components, including thylakoid membranes, carboxysomes and polyribosomes, as well as phages, inside the congested cytosol of the infected cell. By correlating the structural features and relative abundance of viral progeny within cells at different stages of infection, we identified distinct Syn5 assembly intermediates. Our results suggest that the procapsid releases scaffolding proteins and expands its volume at an early stage of genome packaging. Later in assembly, we detected full particles with a tail either with or without an additional horn. The morphogenetic pathway we describe herein is highly conserved and was probably established long before that of double stranded DNA (dsDNA) viruses infecting higher life forms.